Nursing team and promotion of humanized care in a neonatal unit - Jose Hernevides Pontes Ferreira; João Joaquim Freitas do Amaral; Márcia Maria Coelho de Oliveira Lopes (Rev Rene)
Objective: to understand the knowledge and actions of the nursing team about humanized care in a Neonatal Intensive Care Center. Methods: qualitative research carried out with 14 nurses and 20 nursing technicians working in a public institution. Semi-structured interview and content analysis were applied. Results: three thematic categories emerged: Humanized care to the newborn; Welcoming the newborn’s family and Promotion of the neonatal environment. The work of the Nursing team showed they have technical-scientific knowledge, humanized skills and attitudes that provided the recovery of the newborn’s health, minimized the stressors in the neonatal environment, as well as fostered family relationships and establishment of bond during the process of taking care. Conclusion: the acquisition of knowledge about humanized care implied a greater commitment, sensitivity and zeal in the art of taking care, emphasizing, above all, actions of comfort, newborn safety, welcoming to the family and attention in the ambience.